Uma arqueologia do modernismo brasileiro: o discurso da arquitetura nos seus fragmentos textuais e múltiplos vetores que compõem o seu acontecimento - Webbert Soares Caldeira (2007)
The dissertation analyzes the discourse in the golden age of Brazilian modern architecture. The aim is to verify, highlight, and analyze part of the constitution of the knowledge of this period. The philosophical universe of Michel Foucault is the recurring theoretical landmark whose archeological method was emphasized and that, unlike the traditional hermeneutics, does not seek what is hidden in the discourse. A temporary genealogy of the Brazilian modern architecture is presented, consisting of multiple occurrences. Foucaults contribution is connected to the thinking of the difference. This comprehends the being as a fragile category, as opposed to the metaphysical tradition that considers it a unification. Based on Nietzsche and Heidegger, thinking the difference subtracts this supposed unit, freeing the being in its multiplicity, temporality, absence, and appearance. In Foucault, a type of finiteness based on the elements not having the being as author emerges, which conditions the new relations among the subject, the statement, and the history. His thinking attributes to the statements based on the same discursive formation the concept of discourse, and to the management between statements and visibilities the sense of knowledge. The dissertation characterized the discourse formation of the golden age of Brazilian modern architecture in its objects, modes of statements, concepts, and strategies. Three discontinuities between the 1920s and the present days have been highlighted. In the beginning, the subject lacked the experience with the object and was immersed in the idealization of a material culture for the Brazilian architecture. With the firstmodern constructions came the specificity of each work, its discovery by the other foreigner, and the relation between architecture and the Brazilian State. Once the hegemony of the new architecture was affirmed, it became alterity itself. With the exhaustion of the Brazilian modern paradigm in the post-Brasilia, there was the last discontinuity, marked by the discourse of reminiscence. The descentralization of the subject in the selected textual fragments is linked to categories such as temporality, differentiation, discovery, recognition, alterity, exhaustion, and reminiscence. The architecture and its discourse require specific investigation, which makes it necessary, in the conclusion of the work,to proceed in the direction of a more comprehensive genealogy of Brazilian modernism. In this new project, the architectural work must be seen as locus and material synthesis of the power systems involving it. In an inverse dislocation, the creation of its identity will be investigated in the regions with a possible absence of these forces, defining it as a fundamental experience.